ARANSEMEN NICOLAI VARFOLOMEYEFF ATAS LAGU NYIUR HIJAU CIPTAAN MALADI: KAJIAN MUSIKOLOGIS - Diah Uswatun Nurhayati (SURYA SENI, 2007)
Nicolai Varfolomeyeffs arrangement on Maladi’s Nyiur Hijau is one of the products of this Russian musician since he resided in Indonesia during the national independence era. Maladi, who composed this song in 1945, was a nationalist ﬁghter for national freedom, and he later became one of the ministers under Sukarno’s administration. The song of Nyiur Hijau is very popular in the community. As a national song, it is a cultural asset, which becomes a compulsory song in musical contests; it is sung in schools, college and universities; it is aregularly broadcasted by RRI and TVRI, and it was popular among the audience of musical concerts.Nicolai is very well know in the community, especially amongst the community of music educator, as a teacher of cello, a great composer, and a conductor.In fact, he was also very good at composing music, particularly of Russian  style.Due to some political consideration at that time, however,he chose to arrange Indonesia songs only.That’s why he was better known for his arrangement ofsong such as: Kupinta Lagi, Ati Raja and Bengawan Solo. Asa graduate of the famous Moscow Conservatory, Nicolai was very talented and at arranging music to enhance the music’sbeauty.As a music teacher, orchestra, and the science of orchestraat SMIND/AMI (Sekolah Musik Indonesia/Akademi Musik Indonesia) in 1952-1970. He received an art award from the provincial government of Yogyakarta Special Province in 1993, although he had already passed away and he was buried in Sasana Laya Yogyakarta.His life in Yogyakarta was totally dedicated to teaching and developing Western music and upgrading Indonesia music.There are plenty of Nicolai’s works, but most of whose documents are  missing. Apart from the fact that it is still played, Nyiur Hijau is selected as the object of this research because of several considerations, such as its existing score,its popularity, available resources, its creative arrangement, and the writer’s experience with the arrangement. Nicolai creativity was amazing when he worked on NyiurHijau, he was capable of illustrating various moods through the instruments, which ‘sing’ like human voice. This repertoire consist of orchestra and choir as a unity like a piece of symphony.Sound effect and voice in his arrangement can be imagined as Nicolai’s optimism, as a great musician whose ambition is to build Indonesia music to be equal to word-class music.Keywords: arrangement, creativity